Ways to improve the programs of development tourism in Kazakhstan - Batyrova, N.T.; Mombekova, G.R.; Yılmaz, Yaşar; Yerzhanova, S.K. (KSU Publ., 2018)
The article notes that at present tourism is becoming one of the fastest growing sectors of the economy and the direction of the concept of tourism development in Kazakhstan is also topical. The author determined that the hospitality sector began to provide more jobs. This situation affects many countries for the development of tourism. The article considers the systems of evaluation of the concept of tourism development in Kazakhstan until 2020. The tasks and mission of the concept are explored, which are concentrated in five points: creating a framework for new tourism experience, developing ecotourism, environmental education, creating professional management and regulation that provides easy access to Kazakhstan within the country, promoting global competitive services and travel goods. It is concluded that the development of domestic tourism in Kazakhstan will depend on a number of market trends - in the field of tourism in general, economics, demography, ecology, technology and other factors. Therefore, this strategy will be evaluated in accordance with the framework that will be considered in three groups, such as suitability, acceptability and feasibility. The results of this study show positive changes in the main indicators of international tourism, however, we can conclude that the potential of the Kazakh tourism industry is not fully realized.
Қазақстандағы туризмді дамыту бағдарламасын жетілдіру жолдары
Пути совершенствования программы развития туризма в Казахстане
Keywords: tourism; development; economy; analyze; destination; management; strategy; sector; provide; framework